Vasily V. Nalimov – A Scientist, Philosopher and “Mystical Anarchist” from Komi - Menzel, Birgit (Esotericism and Deviance, 2023)
The Russian mathematician, philosopher and visionary Vasily Nalimov (1910–1997) was a Soviet scientist who lived a life of radical pacifism and non-conformism. Not only was he a member of an ethnic minority, but also a life-long esoteric practitioner who belonged to a secret society of mystical anarchists. Nalimov experienced repression in Siberia for a great part of his life, but was eventually allowed to rise to the top of Soviet cybernetics. He became internationally known with part of his mathematical work, while his philosophical writings were suppressed in the USSR. This article is one of the first scholarly publications about Nalimov.<br